The canonical relationship between morphological characteristics and performance of technical elements of goal shooting in water polo game - Nurkovic, N.; Imamovic-Turkovic, D.; Mirvic, E. (Sportski Logos, 2021)
The main goal of this research is to determine and explain the connection between morphological characteristics and derivation of technical elements of goal shooting in water polo. The sample of respondents includes 80 water polo players from Water Polo Clubs Sarajevo City Club, Varepolo Club Torpedo, Water Polo Club Academy, and Water Polo Club Dabar. The test included a sample of 80 water polo players, registered in Bosnian- Herzegovinian clubs. The selection of manifest measures for the assessment of individual latent traits is presented according to the following: Variables for assessing the longitudinal characteristics of the human body: Body height (VISTJ), Leg length (DUZNG), Arm length (DUZRK). Variables for assessing the transference characteristics of the human body: Hand width (SIRSA), Wrist diameter (DIRZG), Elbow diameter (DILAK). Variable for estimating human body mass (weight): Body mass (MASTJ). Variables for assessing circular characteristics of the human body: Upper arm circumference (OBNDL). Medium chest circumference (OBGRU). Variables for the assessment of subcutaneous adipose tissue of the human body: Skinfold of the upper arm (NBNDL), Skinfold of the back (NBLED), and skin fold of the abdomen (NBTRB). A sample of variables to assess the performance of the technical elements of goal-scoring in a water polo game. Goal shot accuracy test: Shooting from the left-wing, from a static position from six (6) meters - STLK, shooting from the center, from a static position from six (6) meters - STC and shooting from the right-wing, from a static position from six (6) meters - STDK. It can be said that the canonical-correlation analysis obtained a significant and homogeneous structure of the connection between a set of morphological characteristics and a set of deriving technical elements of goal shooting.